2019
DOI: 10.1016/j.jtbi.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Cell pelotons: A model of early evolutionary cell sorting, with application to slime mold Dictyostelium discoideum

Abstract: A theoretical model is presented for early evolutionary cell sorting within cellular aggregates. The model involves an energy-saving mechanism and principles of collective self-organization analogous to those observed in bicycle pelotons (groups of cyclists). The theoretical framework is applied to slime-mold slugs (Dictyostelium discoideum) and incorporated into a computer simulation which demonstrates principally the sorting of cells between the anterior and posterior slug regions. The simulation relies on a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…(2014), who demonstrated that hydrodynamic drafting can lead to collective behaviour even in inanimate particles in the liquid. Furthermore, it has been proposed that cells of the slime mould Dictyostelium discoideum form queues in the absence of chemotaxis in order to conserve energy (Trenchard 2019). Hence, it is likely that chemotaxis was a derived character of T. chopini .…”
Section: Discussionmentioning
confidence: 99%
“…(2014), who demonstrated that hydrodynamic drafting can lead to collective behaviour even in inanimate particles in the liquid. Furthermore, it has been proposed that cells of the slime mould Dictyostelium discoideum form queues in the absence of chemotaxis in order to conserve energy (Trenchard 2019). Hence, it is likely that chemotaxis was a derived character of T. chopini .…”
Section: Discussionmentioning
confidence: 99%
“…Hogeweg, Marée, and co-workers combined agent-based and generic mechanisms—chemotaxis to cyclic AMP, differential adhesion and pressure generation—to simulate the aggregation of cells, the correct spatial distribution of cell type and their self-organization into a fruiting body [ 84 , 152 – 154 ]. Trenchard [ 155 ] has proposed a different agent-based mechanism for sorting, one that depends on differences in speeds of movement and energetics.…”
Section: Interplay Of Generic Properties and Agent Behaviorsmentioning
confidence: 99%